2004
DOI: 10.1142/s1088424604000672
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sulfonated phthalocyanines by mass spectrometry and capillary electrophoresis

Abstract: We report the characterization of sulfonated phthalocyanines using capillary electrophoresis and mass spectrometry. Derivatives investigated included the copper, cobalt, zinc and metal-free sulfonated phthalocyanines. In general, sulfonated phthalocyanines were found as aggregates in capillary electrophoresis separations, even at low concentration. Separations were much better at pH 9.0 than at pH 2.5. The addition of β-cyclodextrin did not alter the electropherograms significantly. The electropherograms of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…As reported previously, the negative ion MALDI (CHCA matrix) of T2Nap5S showed a very simple, clear pattern for the tetrasulfonic acid (1134, M À ) and its mono-, di-and trisodium salts [38]. The pentasulfonic acid (1214, M À ) and its mono-, di-, tri-, and tetrasodium salts were also seen.…”
Section: Mass Spectrometry: Effect Of Central Metal Ionsupporting
confidence: 73%
See 2 more Smart Citations
“…As reported previously, the negative ion MALDI (CHCA matrix) of T2Nap5S showed a very simple, clear pattern for the tetrasulfonic acid (1134, M À ) and its mono-, di-and trisodium salts [38]. The pentasulfonic acid (1214, M À ) and its mono-, di-, tri-, and tetrasodium salts were also seen.…”
Section: Mass Spectrometry: Effect Of Central Metal Ionsupporting
confidence: 73%
“…This may reflect the conformations of the 1-naphthyl groups, which extend above and beneath the porphyrin plane, reducing selfstacking. Previous work has shown that self-stacking reduces the CE separation of tetrapyrroles [38]. In the 2-naphthyl series, separation was aided significantly by the addition of cyclodextrins; b-and c-cyclodextrins gave quite different patterns.…”
Section: Ce Separationmentioning
confidence: 91%
See 1 more Smart Citation
“…We used aromatic chelating agents, such as tetrakis(4-carboxyphenyl)porphyrin (TCPP) and tetraphenylporphyrin tetrasulfonate (TPPS), which are water-soluble porphyrins used for the fluorescence detection of metal ions, 8,9 and bathocuproinesulfonate (BCS), which is a phenanthroline that selectively binds copper ions 10 ( Fig. S1, Supporting Information).…”
Section: +mentioning
confidence: 99%
“…Besides, the cis-and trans-isomers with identical sulfonated groups can also be distinguished by their retention time, and the trans-isomer should pass through the column firstly. Dixon et al [10] tried to separate some sulfonated phthalocyanines with capillary electrophoresis method, but the result was unsatisfactory. To our knowledge so far, baseline separation of such substituted phthalocyanine isomers has not been achieved in the literature [11 14] .…”
mentioning
confidence: 99%